2020
DOI: 10.1021/acs.jpca.0c04029
|View full text |Cite
|
Sign up to set email alerts
|

State-to-State Master Equation and Direct Molecular Simulation Study of Energy Transfer and Dissociation for the N2–N System

Abstract: We present a detailed comparison of two high-fidelity approaches for simulating non-equilibrium chemical processes in gases: the state-to-state master equation (StS-ME) and the direct molecular simulation (DMS) methods. The former is a deterministic method, which relies on the pre-computed kinetic database for the N2–N system based on the NASA Ames ab initio potential energy surface (PES) to describe the evolution of the molecules’ internal energy states through a system of master equations. The latter is a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 80 publications
(175 reference statements)
2
12
0
Order By: Relevance
“…Figure compares the present dissociation rate coefficients with the existing data. ,,,,, For both chemical systems, the QSS rate coefficients have slightly lower values than the equilibrium ones, which is consistent with the results obtained for the N 2 + N , and O 2 + O systems. For the N 2 + O system, the measured N 2 + N dissociation rate coefficients are employed in the comparison due to the lack of experimental data for the N 2 + O system.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure compares the present dissociation rate coefficients with the existing data. ,,,,, For both chemical systems, the QSS rate coefficients have slightly lower values than the equilibrium ones, which is consistent with the results obtained for the N 2 + N , and O 2 + O systems. For the N 2 + O system, the measured N 2 + N dissociation rate coefficients are employed in the comparison due to the lack of experimental data for the N 2 + O system.…”
Section: Resultssupporting
confidence: 89%
“…The present calculations predict lower values than the measured ones for both QSS and equilibrium. Interestingly, the present QSS dissociation rate coefficients in N 2 + O interactions are close to those for N 2 + N. , This seems to confirm the possible similarity in physical behavior among different chemical systems that have been discussed in detail in Sections and 3.2. In Figure S8, the PES cuts for N 2 O and N 3 are provided around one of the local minima locations of N 2 O 3 A′.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The present average rotational energy profile shows a larger discrepancy from the DMS result than the vibration during the non-equilibrium energy transfer. According to the previous studies by Venturi et al 2 and Macdonald et al 32 , it was demonstrated that the StS master equation approach yields very similar results with those from the DMS provided that the identical PES is adopted.…”
Section: Application To Combined O 3 +O 4 Systemmentioning
confidence: 92%
“…Gordon & McBride (1994), the rates of vibrational excitation and dissociation have required complex measurements in shock tubes and other devices, although recent developments employing sophisticated theoretical methods to obtain the relevant data have been quite successful, see e.g. Macdonald et al (2020) and Chaudry et al (2020). Nevertheless, the uncertainties associated with dissociation rates remain so high that they are usually quoted as error margins of ±0.2 or so in the power of 10.…”
Section: Introductionmentioning
confidence: 99%